Brazilian Gold and the Lisbon Mint House (1720-1807) - Sousa (2009)
The purpose of this article is to present the official registers of the arrival of Brazilian gold in Portugal, the Livros dos Manifestos do 1% do ouro do Brasil, which are part of a documentary database that exists at the Lisbon Mint House. Discussion of this source and the data provided by it can contribute towards a better historiographic understanding of the issues related to precious metals. The intention here is also to make a comparative analysis between the statistical series already available about the flow of gold across the Atlantic to Portugal and the data available about Spain, facilitating comparisons between the production of the official sources for gold and silver in the two countries. Contrary to what happened in the case of the Casa de la Contratación, which lost control over cargoes after 1668, the Portuguese legislation always afforded the Lisbon Mint House a relatively centralizing role in the receipt of gold remittances. The first section of this article describes the institutional framework behind the source of the Livros dos Manifestos, making a comparison with Spain, which did not lose its relative homogeneity in spite of the changes introduced through legislative procedures. In the second section, a comparison is made between this official source and the results provided by other statistical series describing gold flows at that time. The period under scrutiny is that between 1720 and 1807. The beginning of this time scale is explained by the centralization policy introduced in 1720 when a 1% tax first began to be levied on the value of the gold shipped to Lisbon. The Livros dos Manifestos ended in 1807, when gold ceased to be a source of tax revenue for the budgets of the Portuguese state.